Acute Effects of Particulate Air Pollution on Ischemic Stroke and Hemorrhagic Stroke Mortality - Zhang, Runhua; Liu, Gaifen; Jiang, Yong; Li, Gang; Pan, Yuesong; Wang, Yilong; Wei, Zaihua; Wang, Jing; Wang, Yongjun (Frontiers in Neurology, 2018)
Background and Purpose: A large body of literature reported the association of particulate matter (PM) with stroke in high-income countries. Few studies have examined the association between PM and stroke in middle- and low-income countries and considered the types of stroke. In this study, we examined the short-term effects of particulate matter <2.5 μm in diameter (PM2.5) and particulate matter <10 μm in diameter (PM10) on ischemic stroke mortality and hemorrhagic stroke mortality in Beijing, China. Methods: We used an ecological study design and quasi-Poisson generalized additive models to evaluate the association of PM2.5 and PM10 and cerebrovascular diseases mortality, as well as ischemic- and hemorrhagic stroke mortality. In the model, we controlled long-term and season trends, temperature, and relative humidity, the day of the week and air pollution. For cerebrovascular diseases mortality, we examined the effects stratified by sex and age with different lag days. Results: A total of 48,122 deaths for cerebrovascular disease (32,799 deaths for ischemic stroke and 13,051 deaths for hemorrhagic stroke) were included in the study. PM2.5 was associated with stroke mortality. The 10 μg/m3 increase of PM2.5 was associated with the increase of mortality, 0.27% (95% CI, 0.12–0.43%) for cerebrovascular diseases, 0.23% (95% CI, 0.04–0.42%) for ischemic stroke and 0.37% (95% CI, 0.07–0.67%) for hemorrhagic stroke -. The associations between PM10 and mortality were also detected for cerebrovascular diseases and ischemic stroke, but not in hemorrhagic stroke. The stratified analysis suggested age and gender did not modify the effects of PM on mortality significantly. Conclusions: Our study suggested that short-term exposure to ambient PM was associated with the risk of stroke mortality.